Bridging Theory and Practice in Basic of Educational Management Course: An Action Learning–Based Module to Develop 21st Century Skills - Trihantoyo, Syunu; Widiyanah, Ima; Pattipeilohy, Poltjes; Cindy, Agustin Hanivia; Ardhian, Nur Luthfi; Sa’ari, Akhmarisha (IKIP Widya Darma Surabaya, 2026)
Objective: This study aims to design and evaluate an action learning–based instructional module to address the persistent gap between theoretical understanding and practical competence in basic of educational management course. The study also seeks to answer the research question of how a systematically developed action learning module can enhance student engagement, learning outcomes, and the development of 21st century skills in undergraduate educational management courses. Method: A research and development approach was employed using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages. Data were collected through expert validation, student surveys, classroom observations, and pre-test and post-test assessments to examine the module’s validity, practicality, and effectiveness. Results: Indicate that the instructional module demonstrated high validity and practicality, with expert evaluation scores exceeding a mean value of 4.20 and positive student perceptions regarding clarity, usability, and learning engagement. Implementation findings show notable improvements in student participation, collaborative problem-solving, and confidence in articulating managerial arguments. Furthermore, learning outcome analysis reveals a significant increase in academic achievement, with an average gain of 17.4 points in post-test scores compared to pre-test results. Novelty: The novelty of this study lies in positioning action learning as an instructional design framework embedded within a systematically developed and evaluated module, offering empirical evidence of its effectiveness in fostering 21st century skills in basic of educational management course.